Current Knowledge on CRISPR Strategies Against Antimicrobial-Resistant Bacteria - Carlos de la Fuente Tagarro; Diego Martín-González; Andrea De Lucas; Sergio Bordel; Fernando Santos-Beneit (Antibiotics)
CRISPR/Cas systems have emerged as valuable tools to approach the problem of antimicrobial resistance by either sensitizing or lysing resistant bacteria or by aiding in antibiotic development, with successful applications across diverse organisms, including bacteria and fungi. CRISPR/Cas systems can target plasmids or the bacterial chromosome of AMR-bacteria, and it is especially necessary to have an efficient entry into the target cells, which can be achieved through nanoparticles or bacteriophages. Regarding antibiotic development and production, though the use of CRISPR/Cas in this field is still modest, there is an untapped reservoir of bacterial and fungal natural products, with over 95% yet to be characterized. In Streptomyces, a key antibiotic-producing bacterial genus, CRISPR/Cas has been successfully used to activate silent biosynthetic gene clusters, leading to the discovery of new antibiotics. CRISPR/Cas is also applicable to non-model bacteria and different species of fungi, making it a versatile tool for natural products discovery. Moreover, CRISPR/Cas-based studies offer insights into metabolic regulation and biosynthetic pathways in both bacteria and fungi, highlighting its utility in understanding genetic regulation and improving industrial strains. In this work, we review ongoing innovations on ways to treat antimicrobial resistances and on antibiotic discovery using CRISPR/Cas platforms, highlighting the role of bacteria and fungi in these processes.